Expression of human telomerase catalytic protein in gallbladder carcinogenesis. Issue 8 (27th July 2005) - Luzar, B; Poljak, M; Cör, A; Klopc̆ic̆, U; Ferlan-Marolt, V
Abstract : Background: Telomerase catalytic subunit (hTERT) gene re-expression is a rate limiting step for the activity of telomerase, a key enzyme implicated in cellular immortalisation and transformation. Aims: To determine the potential role of hTERT protein in gallbladder carcinogenesis. Material/Methods: hTERT protein was analysed by means of immunohistochemistry in 89 gallbladder tissue samples: 16 normal epithelia, 14 reactive hyperplasias, 15 low grade dysplasias, 16 high grade dysplasias, and 28 adenocarcinomas. At least 200 nuclei were assessed for each slide and the mean number of positive signals for each nucleus was expressed as the hTERT index. Results: The mean hTERT index increased progressively with the degree of gallbladder epithelial abnormalities: from 0.03 in normal epithelia, 0.04 in hyperplastic epithelia, 0.25 in low grade dysplasia, 0.82 in high grade dysplasia, to 0.93 in adenocarcinoma. Statistical analysis revealed that three different groups of gallbladder epithelial changes can be distinguished according to the number of hTERT signals for each nucleus: (1) normal and regenerative gallbladder epithelium, (2) low grade dysplasia, and (3) high grade dysplasia and adenocarcinoma (p < 0.001). Conclusions: The occasional presence of hTERT protein in normal and regenerative gallbladder mucosa reflects their regenerative capacity. Nevertheless, significantly higher hTERT indices in low and high grade dysplastic epithelia and in gallbladder adenocarcinomas are probably a consequence of hTERT re-expression—an early event in the multistep process of gallbladder carcinogenesis.